The Relationship Between Professional Burnout and Quality and Safety in Healthcare: A Meta-Analysis - Salyers, Michelle P. (J Gen Intern Med, 2016)
BACKGROUND: Healthcare provider burnout is considered a factor in quality of care, yet little is known about the consistency and magnitude of this relationship. This meta-analysis examined relationships between provider burnout (emotional exhaustion, depersonalization, and reduced personal accomplishment) and the quality (perceived quality, patient satisfaction) and safety of healthcare. METHODS: Publications were identified through targeted literature searches in Ovid MEDLINE, PsycINFO, Web of Science, CINAHL, and ProQuest Dissertations & Theses through March of 2015. Two coders extracted data to calculate effect sizes and potential moderators. We calculated Pearson’s r for all independent relationships between burnout and quality measures, using a random effects model. Data were assessed for potential impact of study rigor, outliers, and publication bias. RESULTS: Eighty-two studies including 210,669 healthcare providers were included. Statistically significant negative relationships emerged between burnout and quality (r = −0.26, 95 % CI [−0.29, −0.23]) and safety (r = −0.23, 95 % CI [−0.28, −0.17]). In both cases, the negative relationship implied that greater burnout among healthcare providers was associated with poorer-quality healthcare and reduced safety for patients. Moderators for the quality relationship included dimension of burnout, unit of analysis, and quality data source. Moderators for the relationship between burnout and safety were safety indicator type, population, and country. Rigor of the study was not a significant moderator. DISCUSSION: This is the first study to systematically, quantitatively analyze the links between healthcare provider burnout and healthcare quality and safety across disciplines. Provider burnout shows consistent negative relationships with perceived quality (including patient satisfaction), quality indicators, and perceptions of safety. Though the effects are small to medium, the findings highlight the importance of effective burnout interventions for healthcare providers. Moderator analyses suggest contextual factors to consider for future study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-016-3886-9) contains supplementary material, which is available to authorized users.